Preparation method of anti-dripping colored flame-retardant polyester fiber
By reacting α-ZrP-PDI anti-droplet colored flame retardant molecules in polyester fibers with pre-studded intercalation treatment with PDI amino derivatives, the problem of polyester fibers melting and toxic smoke release at high temperatures is solved, and the combination of efficient flame retardant, anti-droplet and colored properties is achieved, improving the safety performance and aesthetics of the fibers.
Patent Information
- Application Number
- CN202411960893.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-30
AI Technical Summary
Polyester fibers are prone to melt and drip at high temperatures, increasing the risk of fire spread and may release toxic smoke during combustion, affecting human health.
By reacting the α-ZrP treated with the small molecule amine pre-supported intercalation with the PDI amino derivative, an α-ZrP-PDI anti-droplet colored flame retardant molecule is formed, and blended with the polyester slice powder matrix, and finally, an anti-droplet colored flame retardant polyester fiber is prepared by melt spinning process.
It significantly improves the flame retardant properties and droplet resistance of the fiber, while giving the fiber a bright color, meeting the market's demand for color diversity, and improving safety performance and aesthetics while maintaining mechanical properties.
Smart Images

Figure CN119777021A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of functional textile materials and relates to a method for preparing anti-drip colored flame-retardant polyester fiber. Background Art
[0002] Polyester fibers, with their excellent physical properties and chemical stability, have become one of the most widely used synthetic fibers in the textile industry. They are widely used in making clothing, home textiles, industrial textiles, etc.
[0003] Although polyester fiber has many advantages, it is easy to melt and drip at high temperatures. This characteristic may cause the fire to spread rapidly in the event of a fire, increasing safety risks. In addition, polyester fiber may release toxic smoke during combustion, posing a threat to human health. Therefore, improving the flame retardant and anti-melting properties of polyester fiber is of great significance to enhance its application value in fields with higher safety requirements.
[0004] At present, blending flame retardant modification is an effective method for flame retardant modification of polyester fibers. This method is to mix flame retardants with polyester chips and then prepare flame retardant fibers through a melt spinning process. This method can improve the flame retardant properties of the fiber to a certain extent, but there are also some challenges, such as the uniformity of the dispersion of the flame retardant, the compatibility of the flame retardant with the polyester substrate, and how to maintain the mechanical properties of the fiber.
[0005] In order to solve the above problems, patent CN202211327836.3 discloses a solution-dyed regenerated colored flame-retardant polyester flat filament and a preparation method thereof, so as to obtain colored polyester filament with better flame retardant effect and higher dyeing color fastness. However, this patent is for colored flame retardant and does not reflect the anti-dripping function.
[0006] In addition, patent CN202311844723.5 discloses a different shrinkage flame retardant and anti-melt dripping fiber and its preparation method, which obtains a fiber with excellent wool-like effect, flame retardant and anti-melt dripping functions. However, the fiber in this patent is a flame retardant and anti-melt dripping fiber and does not have a color function.
[0007] Therefore, it is of great significance to study a method for preparing a droplet-resistant colored flame-retardant polyester fiber to solve the problems existing in the prior art. Summary of the invention
[0008] The purpose of the invention is to solve the problems existing in the prior art and provide a method for preparing anti-drip colored flame-retardant polyester fiber.
[0009] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0010] A method for preparing an anti-drip colored flame-retardant polyester fiber comprises the following steps: firstly reacting α-ZrP (α-zirconium phosphate) treated with a small molecule amine pre-support intercalation layer with a PDI (perylene diimide) amino derivative to obtain an α-ZrP-PDI anti-drip colored flame-retardant molecule; then blending the α-ZrP-PDI anti-drip colored flame-retardant molecule with a polyester chip powder matrix to obtain an anti-drip colored flame-retardant masterbatch; and finally blending the anti-drip colored flame-retardant masterbatch with the polyester chip and then melt-spinning the blended polyester chip to obtain an anti-drip colored flame-retardant polyester fiber.
[0011] PDI amino derivatives refer to PDI derivatives with -NH2 terminal groups.
[0012] Since the present invention is a single added anti-melting drop flame retardant molecule, it is easier to achieve uniform dispersion in the polyester matrix compared with conventional multi-component addition, thereby ensuring that the mechanical properties of the fiber are not affected, while improving the flame retardant and anti-melting drop properties of the fiber. In the traditional method of achieving colored fiber by adding masterbatch, the addition of flame retardant components and colored components may affect the fiber forming process, or be detrimental to the improvement or even maintenance of flame retardant properties. The α-ZrP-PDI designed and synthesized in the present invention integrates flame retardant and colored functions. By adding a single component, it is more conducive to the uniformity of blending and the stability of fiber forming, and its colored functional component PDI can also synergistically increase the anti-melting drop performance.
[0013] As the preferred technical solution:
[0014] In the method for preparing the anti-drip colored flame-retardant polyester fiber as described above, the molecular structure of the PDI amino derivative is as follows:
[0015]
[0016] The preparation method of the anti-drip colored flame-retardant polyester fiber as described above, the preparation steps of the α-ZrP-PDI anti-drip colored flame-retardant molecule are as follows:
[0017] (1) Perylene tetracarboxylic dianhydride (PTCDA) and ethylenediamine are heated in an imidazole solvent (imidazole is in a molten state at 100 to 110° C. and can be used as a solvent) under a nitrogen atmosphere for 4 to 6 hours, and then ethanol is added to wash away the imidazole precipitated product, and the solid is filtered and dried to obtain a PDI amino derivative;
[0018] (2) After α-ZrP is stirred evenly in an ethanol solvent, a small molecular amine is added and reacted for 1.5 to 2 hours to achieve a pre-supported intercalation treatment of α-ZrP;
[0019] (3) adding the PDI amino derivative obtained in step (1) to the system after the reaction in step (2), stirring the reaction for 8 to 12 hours, filtering and drying to obtain the α-ZrP-PDI anti-drip colored flame retardant molecule.
[0020] In the method for preparing the anti-drip colored flame-retardant polyester fiber as described above, the molar ratio of perylene tetracarboxylic dianhydride to ethylenediamine is 1:1-3, the molar ratio of α-ZrP to small molecule amine is 4:1-4, and the molar ratio of PDI amino derivative to α-ZrP is 1:0.5-1.
[0021] In the method for preparing the anti-drip colored flame-retardant polyester fiber as described above, the small molecule amine is ethylamine, propylamine or butylamine.
[0022] The method for preparing the anti-drip colored flame-retardant polyester fiber as described above takes the total mass of the α-ZrP-PDI anti-drip colored flame-retardant molecules and the polyester chip powder matrix as the benchmark, and the mass percentage of the α-ZrP-PDI anti-drip colored flame-retardant molecules is 30-45%.
[0023] In the method for preparing the anti-drip colored flame-retardant polyester fiber as described above, based on the total amount of the anti-drip colored flame-retardant masterbatch and the polyester chips, the mass percentage of the anti-drip colored flame-retardant masterbatch is 5-15%.
[0024] The preparation method of the anti-drip colored flame-retardant polyester fiber as described above, melt spinning includes a process flow of melt extrusion by a single screw extruder, spinning, cooling, drawing, shaping and winding, and the specific process parameters are as follows:
[0025] The temperature of the single screw extruder: Zone 1 temperature 275-290°C, Zone 2 temperature 285-295°C, Zone 3 temperature 285-295°C, Zone 4 temperature 285-295°C, Zone 5 temperature 285-295°C;
[0026] The spinning temperature is 285-305°C;
[0027] The cooling conditions include: temperature of 15-25°C, relative humidity of 60-75%, and air blowing speed of 0.3-0.8 m / s;
[0028] The drawing ratio of the drawing is 3 to 6 times, the setting temperature is 80 to 110° C., and the winding speed is 2800 to 4200 m / min.
[0029] The method for preparing a melt-drip resistant colored flame-retardant polyester fiber as described above has a limiting oxygen index ≥31%, a vertical burning grade of V0, a melt-drip amount ≤38 mg, a breaking strength ≥4.9 cN / dtex, and a color fastness to washing at 60°C of above grade 4.
[0030] Principle of the invention:
[0031] The present invention realizes the organic combination of flame retardant, anti-melting and colored properties through innovative chemical treatment and blending technology. First, α-ZrP is pre-supported and intercalated with a small molecule amine to increase its interlayer spacing and provide more binding sites for subsequent reactions; then, the pretreated α-ZrP is reacted with a PDI amino derivative, and a large amount of PDI amino derivatives are grafted on the surface and between layers of α-ZrP to form an α-ZrP-PDI anti-melting colored flame retardant molecule. This molecule not only has the colored properties of PDI, but also can form a stable bond with polyester fiber through π-π stacking, thereby enhancing the thermal stability and anti-melting performance of the fiber. At the same time, α-ZrP decomposes at high temperature to release crystal water, take away heat, reduce the material temperature, and block heat and oxygen through the formed protective film, effectively flame retardant. In addition, the layered structure of α-zirconium phosphate and the synergistic effect of Lewis acid points and Bronsted acid points promote carbonization and enhance the thermal stability and mechanical strength of the carbon layer.
[0032] Specifically, α-zirconium phosphate is a material with a layered structure, which gives it unique properties. After pre-intercalation treatment, α-zirconium phosphate still has a layered structure, and the distance between layers increases. In the layered structure of α-zirconium phosphate, there are a large number of Lewis acid sites and Bronsted acid sites, which play a key role in the catalytic, adsorption and flame retardant applications of the material. The Bronsted acid sites come from the H + ions, these H + Ions can diffuse freely in the space within the layer, providing protons (H + ), plays an important role in catalytic reactions. Lewis acid sites usually come from metal cations between α-zirconium phosphate layers, such as Zr 4+ These exposed metal cations can act as electron acceptors and form coordination bonds with molecules containing lone pairs of electrons, thereby exhibiting Lewis acidity.
[0033] The layered structure and acidic sites of α-zirconium phosphate show synergistic effects in catalyzing carbonization and enhancing the thermal stability and mechanical strength of the carbon layer. This synergistic effect not only promotes the carbonization process, but also improves the quality of the carbon layer, making it more stable at high temperatures. Specifically, Bronsted acid sites catalyze the cross-linking of polymers (polyester fibers and other high molecular weight polymers) to form carbon, forming a dense protective layer that blocks the transfer of oxygen and heat, thereby playing a flame retardant role; Bronsted acid sites provide H +It can be used as a catalyst to promote reactions between polymer chains, such as transesterification or amidation, to form new covalent bonds; at high temperatures, polymer chains may break to form free radicals, which can recombine under the catalysis of Bronsted acid points to form a cross-linked structure. Lewis acid points capture macromolecular free radicals, and under the catalysis of Lewis acid points, the captured free radicals can react with other free radicals or polymer chains, prompting them to recombine to form a new cross-linked structure, thereby enhancing the thermal stability and mechanical strength of the carbon layer.
[0034] The synergistic effect of the layered structure and acidic sites of α-zirconium phosphate is crucial for the anti-drip performance. Under high temperature conditions, the acidic sites in the layered structure of α-zirconium phosphate can catalyze the cross-linking of polymers into carbon, forming a dense protective layer. This protective layer can block the mass transfer process of volatile products produced by polymer degradation to the gas phase, and also block the feedback of heat generated by gas phase combustion to the condensed phase, playing a role of heat insulation and oxygen isolation, thereby reducing melting and dripping. This synergistic effect improves the anti-drip performance of polyester fibers, making it less likely to melt and drip in the event of a fire, reducing the risk of fire spread. At the same time, under the action of a large number of PDI amino derivatives grafted on the surface and interlayer of α-zirconium phosphate, it has better interaction with the polymer matrix than α-zirconium phosphate. Therefore, PDI amino derivatives are conducive to connecting polymers with α-zirconium phosphate, accelerating the formation of cross-linking points, thereby inhibiting the flow of polyester during combustion.
[0035] In the present invention, the PDI amino derivative, as a conjugated organic component, is fixed on the surface and interlayer of α-zirconium phosphate, which is conducive to the collision between molecules, thereby forming a dense carbon layer with a high degree of graphitization during the carbonization process, and plays a role in isolating the gas. Therefore, under the dual effects of the PDI amino derivative and α-zirconium phosphate, a condensed flame retardant mechanism of 1+1>2 is formed. After pre-support intercalation, a large amount of PDI amino derivatives can be grafted between the α-zirconium phosphate layers. Both the PDI amino derivative and the α-zirconium phosphate have a certain effect on anti-melting droplets. The PDI amino derivative accelerates the cross-linking point reaction between the α-zirconium phosphate and the polymer, thereby achieving a better anti-melting droplet effect.
[0036] Beneficial effects:
[0037] (1) The present invention discloses a method for preparing a melt-drip resistant colored flame-retardant polyester fiber, which comprises pre-supporting and intercalating α-ZrP with a small molecule amine to increase its interlayer spacing, and then reacting the pre-treated α-ZrP with a PDI amino derivative to form an α-ZrP-PDI melt-drip resistant colored flame-retardant molecule, thereby significantly improving the flame retardant and melt-drip resistant properties of the polyester fiber. At the same time, the present invention also introduces a colored molecular unit to give the fiber a bright color, thereby meeting the market demand for color diversity.
[0038] (2) The present invention provides a method for preparing an anti-melting dripping colored flame-retardant polyester fiber, which achieves flame retardant and anti-melting dripping effects by adding a single anti-melting dripping flame-retardant molecule. The molecule is easy to disperse evenly in the polyester matrix, thereby improving the overall performance of the fiber. At the same time, the molecule has a bright color, which meets the aesthetic requirements of colored fibers.
[0039] (3) The present invention provides a method for preparing a melt-drip resistant colored flame-retardant polyester fiber. The melt-drip resistant colored flame-retardant polyester fiber has better safety performance and aesthetics while maintaining the original mechanical properties, thereby broadening its application prospects in high-end textiles, interior decoration materials and other fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 Schematic diagram of the α-ZrP-PDI anti-drip colored flame retardant molecule prepared by grafting PDI amino derivatives on the surface and interlayer of α-zirconium phosphate;
[0041] Figure 2 X-ray diffraction diagram of α-zirconium phosphate before and after pre-support intercalation;
[0042] Figure 3 This is the infrared spectrum of the α-ZrP-PDI anti-drip colored flame retardant molecule in Example 1. DETAILED DESCRIPTION
[0043] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0044] The test methods involved in the performance indicators in the embodiments and comparative examples of the present invention are as follows:
[0045] Limiting oxygen index: tested according to GB / T 2406.2-2009.
[0046] Vertical burning grade: tested according to GB / T 2408-2008.
[0047] Breaking strength: tested according to GB / T 14344-2008.
[0048] Washing color fastness: tested according to GB / T3921-2008.
[0049] Droplet amount: Referring to the description and test method of droplets in patent CN202411077402.1, the present invention adopts a UL1581 combustion test machine to continuously burn the sample, collects the droplets at the bottom with water, and weighs and detects the droplet amount.
[0050] The polyester chips of the present invention are sourced from: manufacturer: Yizheng Chemical Fiber, brand: polyester fiber grade semi-dull chips TFW100.
[0051] Example 1
[0052] A method for preparing colored flame-retardant polyester fiber with high-efficiency flame-retardant properties, the specific steps are as follows:
[0053] (1) Perylene tetracarboxylic dianhydride and ethylenediamine were heated to react in an imidazole solvent at 100° C. under a nitrogen atmosphere for 6 hours, and then ethanol was added to precipitate the product. The solid was filtered and dried to obtain a PDI amino derivative, whose molecular structure is as follows:
[0054]
[0055] The molar ratio of perylene tetracarboxylic dianhydride to ethylenediamine is 1:1; the amount of ethanol added is 10 times the mass of imidazole; the mass ratio of perylene tetracarboxylic dianhydride to imidazole is 1:25;
[0056] (2) Figure 1 As shown, after α-ZrP is stirred evenly in an ethanol solvent, ethylamine is added and reacted for 1.5 hours to achieve the pre-supported intercalation treatment of α-ZrP;
[0057] The molar ratio of α-ZrP to ethanol solvent is 1:20, and the molar ratio of α-ZrP to small molecule amine is 4:1;
[0058] like Figure 2 As shown, the characteristic diffraction peak 2θ of α-ZrP shifts from 11.62° to 6.03°. By calculation, it can be concluded that the interlayer spacing increases from 0.76nm to 1.46nm, proving that the interlayer spacing increases after α-zirconium phosphate intercalation.
[0059] (3) adding the PDI amino derivative obtained in step (1) to the system after the reaction in step (2), stirring the reaction for 8 hours, filtering and drying to obtain α-ZrP-PDI anti-drip colored flame retardant molecules;
[0060] The molar ratio of PDI amino derivative to α-ZrP was 1:0.5;
[0061] (4) blending the α-ZrP-PDI colored high-efficiency flame-retardant molecule with the polyester chip powder matrix to obtain an anti-drip colored flame-retardant masterbatch;
[0062] Based on the total mass of the α-ZrP-PDI anti-drip colored flame retardant and the polyester chip powder matrix, the mass percentage of the α-ZrP-PDI anti-drip colored flame retardant molecule is 30%;
[0063] like Figure 3 The infrared spectrum shown, 1235cm -1It is the characteristic peak of α-zirconium phosphate, 1595cm -1 The characteristic peak of PDI is 1483 cm -1 The peak is -NH3 + The peak of α-zirconium phosphate was confirmed by the successful grafting of PDI onto α-zirconium phosphate.
[0064] (5) After the anti-melt drip colored flame retardant masterbatch is blended with polyester chips, the process of melt extrusion, spinning, cooling, drawing, shaping and winding are carried out in sequence through a single screw extruder to finally obtain the anti-melt drip colored flame retardant polyester fiber; the specific process parameters are as follows:
[0065] The temperature of the single screw extruder: Zone 1 temperature 275°C, Zone 2 temperature 285°C, Zone 3 temperature 285°C, Zone 4 temperature 285°C, Zone 5 temperature 285°C;
[0066] The spinning temperature is 285°C;
[0067] The cooling conditions included: temperature of 15°C, relative humidity of 60%, and air velocity of 0.3 m / s;
[0068] The drafting ratio is 3 times, the setting temperature is 80°C, and the winding speed is 2800m / min;
[0069] Based on the total amount of the anti-drip colored flame retardant masterbatch and the polyester chips, the mass percentage of the anti-drip colored flame retardant masterbatch is 5%.
[0070] The final anti-drip colored flame-retardant polyester fiber has a limiting oxygen index of 28%, a vertical burning grade of V0, a droplet amount of 38 mg, a breaking strength of 5.5 cN / dtex, and a color fastness to washing at 60°C of level 4.
[0071] Comparative Example 1
[0072] A method for preparing polyester fiber is basically the same as that of Example 1, except that the operation of preparing a PDI amino derivative in step (1) is omitted, that is, the PDI amino derivative is replaced with PDI in step (3), and the masterbatch is prepared by blending a mixture of α-ZrP and PDI with a polyester chip powder matrix in step (4).
[0073] The polyester fiber obtained has a limiting oxygen index of 28%, a vertical burning grade of V0, a droplet amount of 145 mg, a breaking strength of 4.8 cN / dtex, and a color fastness to washing at 60°C of grade 2.
[0074] By comparing Comparative Example 1 with Example 1, it can be found that the color fastness of Comparative Example 1 to water washing decreases, the droplet amount increases, and the breaking strength decreases. This is because PDI cannot form a chemical bond interaction with α-ZrP, and the PDI molecules are small and easily washed away and discolored after water washing; adding multiple substances separately can easily lead to uneven mixing, resulting in some parts of the material without PDI distribution, causing the droplet amount to increase; at the same time, the uneven mixing of multiple substances will cause the mechanical properties of the material to decrease, resulting in a decrease in breaking strength.
[0075] Comparative Example 2
[0076] A method for preparing polyester fiber is basically the same as Example 1, except that the pre-support intercalation treatment of α-ZrP in step (2) is omitted, that is, in step (3), a PDI amino derivative is added to an ethanol dispersion of α-ZrP for reaction.
[0077] The polyester fiber obtained has a limiting oxygen index of 28%, a vertical burning grade of V0, a droplet amount of 215 mg, a breaking strength of 5.5 cN / dtex, and a color fastness to washing at 60°C of grade 4.
[0078] By comparing Comparative Example 2 with Example 1, it can be found that the droplet amount in Comparative Example 2 increases. This is because α-ZrP has not undergone pre-support intercalation treatment, so the molecular layer spacing of α-ZrP is small, and the PDI amino derivative cannot be grafted between the molecular layers of α-ZrP, but can only be grafted to the molecular surface of α-ZrP, which makes the grafting amount of PDI amino derivatives less, resulting in an increase in the droplet amount.
[0079] Comparative Example 3
[0080] A method for preparing polyester fiber is basically the same as that of Example 1, except that the operations of steps (2) and (3) are omitted, and in step (4), a PDI amino derivative is directly blended with a polyester chip powder matrix to prepare a masterbatch.
[0081] The polyester fiber obtained has a limiting oxygen index of 23%, a vertical burning grade of NR, a droplet amount of 178 mg, a breaking strength of 5.8 cN / dtex, and a color fastness to washing at 60°C of grade 2.
[0082] By comparing Comparative Example 3 with Example 1, it can be found that the limiting oxygen index of Comparative Example 3 decreases, the vertical burning level decreases, the droplet amount increases, the breaking strength increases slightly, and the water washing color fastness decreases. This is because when α-ZrP is not added, the flame retardant performance of the material is poor, and the anti-droplet effect decreases, so the limiting oxygen index decreases, the vertical burning level decreases, and the droplet amount increases; at the same time, the addition of inorganic powder such as α-ZrP will lead to a decrease in breaking strength, and the absence of α-ZrP will slightly increase the breaking strength; in addition, the PDI amino derivative has a small molecule, and when there is no inorganic powder α-ZrP fixed in the polyester fiber, it is easy to be washed away and discolored after washing.
[0083] Example 2
[0084] A method for preparing colored flame-retardant polyester fiber with high-efficiency flame-retardant properties, the specific steps are as follows:
[0085] (1) Perylene tetracarboxylic dianhydride and ethylenediamine were heated to react in an imidazole solvent at 105° C. under a nitrogen atmosphere for 5 hours, and then ethanol was added to precipitate the product. The solid was filtered and dried to obtain a PDI amino derivative, whose molecular structure is as follows:
[0086]
[0087] The molar ratio of perylene tetracarboxylic dianhydride to ethylenediamine is 1:2; the amount of ethanol added is 10 times the mass of imidazole; the mass ratio of perylene tetracarboxylic dianhydride to imidazole is 1:25;
[0088] (2) After α-ZrP is stirred evenly in an ethanol solvent, propylamine is added and reacted for 1.75 hours to achieve pre-supported intercalation treatment of α-ZrP;
[0089] The molar ratio of α-ZrP to ethanol solvent is 1:25, and the molar ratio of α-ZrP to small molecule amine is 4:1;
[0090] (3) adding the PDI amino derivative obtained in step (1) to the system after the reaction in step (2), stirring the reaction for 9 hours, filtering and drying to obtain α-ZrP-PDI anti-drip colored flame retardant molecules;
[0091] The molar ratio of PDI amino derivative to α-ZrP was 1:0.6;
[0092] (4) blending the α-ZrP-PDI colored high-efficiency flame-retardant molecule with the polyester chip powder matrix to obtain an anti-drip colored flame-retardant masterbatch;
[0093] Based on the total mass of α-ZrP-PDI anti-drip colored flame retardant and polyester chip powder matrix, the mass percentage of α-ZrP-PDI anti-drip colored flame retardant molecules is 32%.
[0094] (5) After the anti-melt drip colored flame retardant masterbatch is blended with polyester chips, the process of melt extrusion, spinning, cooling, drawing, shaping and winding are carried out in sequence through a single screw extruder to finally obtain the anti-melt drip colored flame retardant polyester fiber; the specific process parameters are as follows:
[0095] The temperature of the single screw extruder: Zone 1 temperature 278°C, Zone 2 temperature 287°C, Zone 3 temperature 287°C, Zone 4 temperature 288°C, Zone 5 temperature 288°C;
[0096] The spinning temperature is 290°C;
[0097] The cooling conditions included: temperature of 18°C, relative humidity of 63%, and air velocity of 0.4 m / s;
[0098] The drafting ratio is 4 times, the setting temperature is 85°C, and the winding speed is 3000m / min;
[0099] Based on the total amount of the anti-drip colored flame retardant masterbatch and the polyester chips, the mass percentage of the anti-drip colored flame retardant masterbatch is 7%.
[0100] The final anti-drip colored flame-retardant polyester fiber has a limiting oxygen index of 31%, a vertical burning grade of V0, a dripping amount of 35 mg, a breaking strength of 5.3 cN / dtex, and a color fastness to washing at 60°C of level 4.
[0101] Example 3
[0102] A method for preparing colored flame-retardant polyester fiber with high-efficiency flame-retardant properties, the specific steps are as follows:
[0103] (1) Perylene tetracarboxylic dianhydride and ethylenediamine were heated to react in an imidazole solvent at 110° C. under a nitrogen atmosphere for 4 hours, and then ethanol was added to precipitate the product. The solid was filtered and dried to obtain a PDI amino derivative, whose molecular structure is as follows:
[0104]
[0105] The molar ratio of perylene tetracarboxylic dianhydride to ethylenediamine is 1:2; the amount of ethanol added is 15 times the mass of imidazole; the mass ratio of perylene tetracarboxylic dianhydride to imidazole is 1:30;
[0106] (2) After α-ZrP is stirred evenly in an ethanol solvent, butylamine is added and reacted for 2 hours to achieve the pre-support intercalation treatment of α-ZrP;
[0107] The molar ratio of α-ZrP to ethanol solvent is 1:25, and the molar ratio of α-ZrP to small molecule amine is 4:2;
[0108] (3) adding the PDI amino derivative obtained in step (1) to the system after the reaction in step (2), stirring the reaction for 10 hours, filtering and drying to obtain α-ZrP-PDI anti-drip colored flame retardant molecules;
[0109] The molar ratio of PDI amino derivative to α-ZrP was 1:0.6;
[0110] (4) blending the α-ZrP-PDI colored high-efficiency flame-retardant molecule with the polyester chip powder matrix to obtain an anti-drip colored flame-retardant masterbatch;
[0111] Based on the total mass of α-ZrP-PDI anti-drip colored flame retardant and polyester chip powder matrix, the mass percentage of α-ZrP-PDI anti-drip colored flame retardant molecules is 36%.
[0112] (5) After the anti-melt drip colored flame retardant masterbatch is blended with polyester chips, the process of melt extrusion, spinning, cooling, drawing, shaping and winding are carried out in sequence through a single screw extruder to finally obtain the anti-melt drip colored flame retardant polyester fiber; the specific process parameters are as follows:
[0113] The temperature of the single screw extruder: Zone 1 temperature 281°C, Zone 2 temperature 289°C, Zone 3 temperature 289°C, Zone 4 temperature 290°C, Zone 5 temperature 290°C;
[0114] The spinning temperature is 295°C;
[0115] The cooling conditions included: temperature of 20°C, relative humidity of 65%, and air velocity of 0.5 m / s;
[0116] The drafting ratio is 4.5 times, the setting temperature is 90°C, and the winding speed is 3400m / min;
[0117] Based on the total amount of the anti-drip colored flame retardant masterbatch and the polyester chips, the mass percentage of the anti-drip colored flame retardant masterbatch is 10%.
[0118] The final anti-drip colored flame-retardant polyester fiber has a limiting oxygen index of 32%, a vertical burning grade of V0, a dripping amount of 34 mg, a breaking strength of 5.2 cN / dtex, and a color fastness to washing at 60°C of level 4.
[0119] Example 4
[0120] A method for preparing colored flame-retardant polyester fiber with high-efficiency flame-retardant properties, the specific steps are as follows:
[0121] (1) Perylene tetracarboxylic dianhydride and ethylenediamine were heated to react in an imidazole solvent at 102° C. under a nitrogen atmosphere for 4.5 hours, and then ethanol was added to precipitate the product. The solid was filtered and dried to obtain a PDI amino derivative, whose molecular structure is as follows:
[0122]
[0123] The molar ratio of perylene tetracarboxylic dianhydride to ethylenediamine is 1:3; the amount of ethanol added is 15 times the mass of imidazole; the mass ratio of perylene tetracarboxylic dianhydride to imidazole is 1:40;
[0124] (2) After α-ZrP is stirred evenly in an ethanol solvent, ethylamine is added and reacted for 2 hours to achieve the pre-support intercalation treatment of α-ZrP;
[0125] The molar ratio of α-ZrP to ethanol solvent is 1:25, and the molar ratio of α-ZrP to small molecule amine is 4:3;
[0126] (3) adding the PDI amino derivative obtained in step (1) to the system after the reaction in step (2), stirring the reaction for 11 hours, filtering and drying to obtain α-ZrP-PDI anti-drip colored flame retardant molecules;
[0127] The molar ratio of PDI amino derivative to α-ZrP was 1:0.8;
[0128] (4) blending the α-ZrP-PDI colored high-efficiency flame-retardant molecule with the polyester chip powder matrix to obtain an anti-drip colored flame-retardant masterbatch;
[0129] Based on the total mass of the α-ZrP-PDI anti-drip colored flame retardant and the polyester chip powder matrix, the mass percentage of the α-ZrP-PDI anti-drip colored flame retardant molecule is 40%;
[0130] (5) After the anti-melt drip colored flame retardant masterbatch is blended with polyester chips, the process of melt extrusion, spinning, cooling, drawing, shaping and winding are carried out in sequence through a single screw extruder to finally obtain the anti-melt drip colored flame retardant polyester fiber; the specific process parameters are as follows:
[0131] The temperature of the single screw extruder: Zone 1 temperature 284°C, Zone 2 temperature 291°C, Zone 3 temperature 291°C, Zone 4 temperature 292°C, Zone 5 temperature 293°C;
[0132] The spinning temperature is 298°C;
[0133] The cooling conditions included: temperature of 22°C, relative humidity of 68%, and air velocity of 0.6 m / s;
[0134] The drafting ratio is 5 times, the setting temperature is 95°C, and the winding speed is 3800m / min;
[0135] Based on the total amount of the anti-drip colored flame retardant masterbatch and the polyester chips, the mass percentage of the anti-drip colored flame retardant masterbatch is 12%.
[0136] The final anti-drip colored flame-retardant polyester fiber has a limiting oxygen index of 35%, a vertical burning grade of V0, a dripping amount of 30 mg, a breaking strength of 5 cN / dtex, and a color fastness to washing at 60°C of grade 4.
[0137] Example 5
[0138] A method for preparing colored flame-retardant polyester fiber with high-efficiency flame-retardant properties, the specific steps are as follows:
[0139] (1) Perylene tetracarboxylic dianhydride and ethylenediamine were heated to react in an imidazole solvent at 104° C. under a nitrogen atmosphere for 4.75 hours, and then ethanol was added to precipitate the product. The solid was filtered and dried to obtain a PDI amino derivative, whose molecular structure is as follows:
[0140]
[0141] The molar ratio of perylene tetracarboxylic dianhydride to ethylenediamine is 1:3; the amount of ethanol added is 20 times the mass of imidazole; the mass ratio of perylene tetracarboxylic dianhydride to imidazole is 1:45;
[0142] (2) After α-ZrP is stirred evenly in an ethanol solvent, propylamine is added and reacted for 1.75 hours to achieve pre-supported intercalation treatment of α-ZrP;
[0143] The molar ratio of α-ZrP to ethanol solvent is 1:30, and the molar ratio of α-ZrP to small molecule amine is 4:3;
[0144] (3) adding the PDI amino derivative obtained in step (1) to the system after the reaction in step (2), stirring the reaction for 12 hours, filtering and drying to obtain α-ZrP-PDI anti-melting colored flame retardant molecules;
[0145] The molar ratio of PDI amino derivative to α-ZrP was 1:0.8;
[0146] (4) blending the α-ZrP-PDI colored high-efficiency flame-retardant molecule with the polyester chip powder matrix to obtain an anti-drip colored flame-retardant masterbatch;
[0147] Based on the total mass of α-ZrP-PDI anti-melting colored flame retardant and polyester chip powder matrix, the mass percentage of α-ZrP-PDI anti-melting colored flame retardant molecules is 42%.
[0148] (5) After the anti-melt drip colored flame retardant masterbatch is blended with polyester chips, the process of melt extrusion, spinning, cooling, drawing, shaping and winding are carried out in sequence through a single screw extruder to finally obtain the anti-melt drip colored flame retardant polyester fiber; the specific process parameters are as follows:
[0149] The temperature of the single screw extruder: Zone 1 temperature 287°C, Zone 2 temperature 293°C, Zone 3 temperature 293°C, Zone 4 temperature 294°C, Zone 5 temperature 294°C;
[0150] The spinning temperature is 300°C;
[0151] The cooling conditions included: temperature of 24°C, relative humidity of 70%, and air velocity of 0.7 m / s;
[0152] The drafting ratio is 5.5 times, the setting temperature is 100°C, and the winding speed is 4000m / min;
[0153] Based on the total amount of the anti-drip colored flame retardant masterbatch and the polyester chips, the mass percentage of the anti-drip colored flame retardant masterbatch is 13%.
[0154] The final anti-drip colored flame-retardant polyester fiber has a limiting oxygen index of 37%, a vertical burning grade of V0, a dripping amount of 25 mg, a breaking strength of 4.9 cN / dtex, and a color fastness to washing at 60°C of grade 4.
[0155] Example 6
[0156] A method for preparing colored flame-retardant polyester fiber with high-efficiency flame-retardant properties, the specific steps are as follows:
[0157] (1) Perylene tetracarboxylic dianhydride and ethylenediamine were heated to react in an imidazole solvent at 108° C. under a nitrogen atmosphere for 5.5 hours, and then ethanol was added to precipitate the product. The solid was filtered and dried to obtain a PDI amino derivative, whose molecular structure is as follows:
[0158]
[0159] The molar ratio of perylene tetracarboxylic dianhydride to ethylenediamine is 1:3; the amount of ethanol added is 20 times the mass of imidazole; the mass ratio of perylene tetracarboxylic dianhydride to imidazole is 1:50;
[0160] (2) After α-ZrP is stirred evenly in an ethanol solvent, butylamine is added and reacted for 1.5 hours to achieve pre-supported intercalation treatment of α-ZrP;
[0161] The molar ratio of α-ZrP to ethanol solvent is 1:30, and the molar ratio of α-ZrP to small molecule amine is 4:4;
[0162] (3) adding the PDI amino derivative obtained in step (1) to the system after the reaction in step (2), stirring the reaction for 10 hours, filtering and drying to obtain α-ZrP-PDI anti-drip colored flame retardant molecules;
[0163] The molar ratio of PDI amino derivative to α-ZrP was 1:1;
[0164] (4) blending the α-ZrP-PDI colored high-efficiency flame-retardant molecule with the polyester chip powder matrix to obtain an anti-drip colored flame-retardant masterbatch;
[0165] Based on the total mass of the α-ZrP-PDI anti-drip colored flame retardant and the polyester chip powder matrix, the mass percentage of the α-ZrP-PDI anti-drip colored flame retardant molecule is 45%;
[0166] (5) After the anti-melt drip colored flame retardant masterbatch is blended with polyester chips, the process of melt extrusion, spinning, cooling, drawing, shaping and winding are carried out in sequence through a single screw extruder to finally obtain the anti-melt drip colored flame retardant polyester fiber; the specific process parameters are as follows:
[0167] The temperature of the single screw extruder: Zone 1 temperature 290°C, Zone 2 temperature 295°C, Zone 3 temperature 295°C, Zone 4 temperature 295°C, Zone 5 temperature 295°C;
[0168] The spinning temperature is 305°C;
[0169] The cooling conditions included: temperature of 25°C, relative humidity of 75%, and air velocity of 0.8 m / s;
[0170] The drafting ratio is 6 times, the setting temperature is 110°C, and the winding speed is 4500m / min;
[0171] Based on the total amount of the anti-drip colored flame retardant masterbatch and the polyester chips, the mass percentage of the anti-drip colored flame retardant masterbatch is 15%.
[0172] The final anti-drip colored flame-retardant polyester fiber has a limiting oxygen index of 38%, a vertical burning grade of V0, a dripping amount of 21 mg, a breaking strength of 4.8 cN / dtex, and a color fastness to washing at 60°C of level 4.
Claims
1. A method for preparing anti-drip colored flame-retardant polyester fiber, characterized in that: Firstly, α-ZrP treated with small molecule amine pre-support intercalation is reacted with PDI amino derivatives to obtain α-ZrP-PDI anti-drip colored flame retardant molecules, then the α-ZrP-PDI anti-drip colored flame retardant molecules are blended with polyester chip powder matrix to obtain anti-drip colored flame retardant masterbatch, and finally the anti-drip colored flame retardant masterbatch is blended with polyester chips and melt-spun to obtain anti-drip colored flame retardant polyester fibers; PDI amino derivatives refer to PDI derivatives with -NH2 terminal groups.
2. The method for preparing a drip-resistant colored flame-retardant polyester fiber according to claim 1, characterized in that: The molecular structure of PDI amino derivatives is as follows:
3. The method for preparing a drip-resistant colored flame-retardant polyester fiber according to claim 1, characterized in that: The preparation steps of α-ZrP-PDI anti-drip colored flame retardant molecules are as follows: (1) heating perylene tetracarboxylic dianhydride and ethylenediamine in an imidazole solvent at 100 to 110° C. in a nitrogen atmosphere for 4 to 6 hours, then adding ethanol to precipitate the product, filtering the solid and drying it to obtain a PDI amino derivative; (2) After α-ZrP is stirred evenly in an ethanol solvent, a small molecular amine is added and reacted for 1.5 to 2 hours to achieve a pre-supported intercalation treatment of α-ZrP; (3) adding the PDI amino derivative obtained in step (1) to the system after the reaction in step (2), stirring the reaction for 8 to 12 hours, filtering and drying to obtain the α-ZrP-PDI anti-drip colored flame retardant molecule.
4. The method for preparing a drip-resistant colored flame-retardant polyester fiber according to claim 3, characterized in that: The molar ratio of perylene tetracarboxylic dianhydride to ethylenediamine is 1:1-3, the molar ratio of α-ZrP to small molecular amine is 4:1-4, and the molar ratio of PDI amino derivative to α-ZrP is 1:0.5-1.
5. The method for preparing a drip-resistant colored flame-retardant polyester fiber according to claim 3, characterized in that: The small molecule amine is ethylamine, propylamine or butylamine.
6. The method for preparing a drip-resistant colored flame-retardant polyester fiber according to claim 1, characterized in that: Based on the total mass of the α-ZrP-PDI anti-drip colored flame retardant molecules and the polyester chip powder matrix, the mass percentage of the α-ZrP-PDI anti-drip colored flame retardant molecules is 30-45%.
7. The method for preparing a drip-resistant colored flame-retardant polyester fiber according to claim 1, characterized in that: Based on the total amount of the anti-drip colored flame retardant masterbatch and the polyester chips, the mass percentage of the anti-drip colored flame retardant masterbatch is 5-15%.
8. The method for preparing a drip-resistant colored flame-retardant polyester fiber according to claim 1, characterized in that: Melt spinning includes the process of melt extrusion, spinning, cooling, drawing, shaping and winding by a single screw extruder. The specific process parameters are as follows: The temperature of the single screw extruder: Zone 1 temperature 275-290°C, Zone 2 temperature 285-295°C, Zone 3 temperature 285-295°C, Zone 4 temperature 285-295°C, Zone 5 temperature 285-295°C; The spinning temperature is 285-305°C; The cooling conditions include: temperature of 15-25°C, relative humidity of 60-75%, and air blowing speed of 0.3-0.8 m / s; The drawing ratio of the drawing is 3 to 6 times, the setting temperature is 80 to 110° C., and the winding speed is 2800 to 4200 m / min.
9. The method for preparing a drip-resistant colored flame-retardant polyester fiber according to claim 1, characterized in that: The limiting oxygen index of the anti-drip colored flame-retardant polyester fiber is ≥31%, the vertical burning grade is V0, the droplet amount is ≤38mg, the breaking strength is ≥4.9cN / dtex, and the color fastness to washing at 60℃ is above grade 4.
Citation Information
Patent Citations
Preparation method for flame-retardant anti-dripping polyester fiber
CN110592709A
Four-arm perylene diimide compound as well as synthesis method and application thereof
CN116947855A
Deodorization fiber and manufacture method thereof
US20240100511A1
Perylene diimide derivative PDIC-NC, preparation method therefor and application thereof
WO2022143183A1
Cited By
DTY fiber and preparation method thereof
CN120925108A